Molecular cloning, characterization and expression of two [beta]-xylanase-encoding genes of the fungus Aspergillus niger in the yeast Saccharomyces cerevisiae - Luttig, Michael (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1996.